Effect of Zinc on the Growth and Essential Oil Composition of Ocimum gratissimum L. Issue 2 (4th March 2019) - Bisht, Mamta; Pande, Chitra; Tewari, Geeta; Bhatt, Sunita; Triphati, Sonal
Abstract: Ocimum gratissimum, commonly known as Rama Tulsi is a rich source of aroma chemicals that find varied application in the food, flavor and pharmaceutical industry. A polyhouse study was conducted to determine the effect of zinc on the growth and essential oil composition of O. gratissimum L. The treatments of zinc were 600, 1000 and 1200 mg kg -1 in triplicate along with a control treatment. Zinc content was examined by AAS while hydrodistilled oil was analyzed by GC and GC-MS. The highest fresh weight and plant height was obtained from the plants grown in control soil. Ocimum gratissimum treated with Zn at a rate of 600 mg kg -1 accumulated greater concentrations of Zn. Thirty four, 36, 36 and 29 compounds constituting 93.62, 85.99, 93.60 and 9525 % of the total oil were identified in the essential oil of control, Zn600, Zn1000 and Zn1200 treatments respectively. The main components in the oil of plants grown in control soil were germacrene D (31.04 %), ( E)- caryophyllene (9.00 %), ( Z)- β-ocimene (8.67 %), α-copaene (8.48 %), eugenol (7.87 %) and caryophyllene oxide (7.03 %). The content of eugenol was found to decrease significantly from 7.87 to 1.99 % while that of maaliol which was absent in the control, increased to 17.65 % with 1200 mg kg -1 of Zn treatment.